GAVeCeLT-WoCoVA Consensus on subcutaneously anchored securement devices for the securement of venous catheters: Current evidence and recommendations for future research. Issue 5 (September 2021) - Pinelli, Fulvio; Pittiruti, Mauro; Van Boxtel, Ton; Barone, Giovanni; Biffi, Roberto; Capozzoli, Giuseppe; Crocoli, Alessandro; Elli, Stefano; Elisei, Daniele; Fabiani, Adam; Garrino, Cristina; Graziano, Ugo; et al.
Background: Subcutaneously anchored securement devices (or subcutaneous engineered securement devices) have been introduced recently into the clinical practice, but the number of published studies is still scarce. The Italian Group of Long-Term Central Venous Access Devices (GAVeCeLT)—in collaboration with WoCoVA (World Congress on Vascular Access)—has developed a Consensus about the effectiveness, safety, and cost-effectiveness of such devices. Methods: After the definition of a panel of experts, a systematic collection and review of the literature on subcutaneously anchored securement devices was performed. The panel has been divided in two working groups, one focusing on adult patients and the other on children and neonates. Results: Although the quality of evidence is generally poor, since it is based mainly on non-controlled prospective studies, the panel has concluded that subcutaneously anchored securement devices are overall effective in reducing the risk of dislodgment and they appear to be safe in all categories of patients, being associated only with rare and negligible local adverse effects; cost-effectiveness is demonstrated—or highly likely—in specific populations of patients with long-term venous access and/or at high risk of dislodgment. Conclusion: Subcutaneously anchored securement is a very promising strategy for avoiding dislodgment. Further studies are warranted, in particular for the purpose of defining (a) the best management of the anchoring device so to avoid local problems, (b) the patient populations in which it may be considered highly cost-effective and even mandatory, (c) the possible benefit in terms of reduction of other catheter-related complications such as venous thrombosis and/or infection, and—last but not least—(d) their impact on the workload and stress level of nurses taking care of the devices.